Lessons from the Front: Working in the Real World - a Seminar Led by Professional Engineers and Fisheries Scientists from the WA Section of the American Water Resources Association - Klug, Jacqueline; Peterson, Beth; Steward, Cleve; Sturtevant, Peter (University of Washington Water Center, 2008)
Klug will provide an overview of the American Water Resources Association. Next, each panelist will describe their educational and work backgrounds. They will also describe a variety of projects they have managed. Finally, they will offer career advice to the students in the audience.
Keywords: water resources; wetland conservation; ecosystem management; environmental engineering; fisheries management; water management; habitat conservation; salmon; water; water quality; career planning; hydrology; nonpoint source pollution; water pollution; pollution control; stormwater management; employment opportunities; writing skills; water policy; water supply